MARTIAL 'IN CALLIMACHVM' (10.4). (8th November 2018) - Cartlidge, Ben
Abstract : This article has the aim of bringing some fresh observations to the interpretation of a Martial epigram. Beyond the individual poem, it seeks to read Martial's poetics more broadly, particularly with regard to the presence of Greek avatars, of various kinds, in his poetic production. The strategy will be an exact reading of the literary avatars in 10.4, with an attempt to specify the tone with which individual writers are associated. Once this strategy is developed in the case of well-recognized intertextual models, it will be used to explore an underrated intertext in 10.4.